ANALYSIS OF THE INFLUENCE OF TIKTOK ON THE MOTIVATION AND INTEREST IN LEARNING DANCE OF GRADE X STUDENTS IN SENIOR HIGH SCHOOL IN BOGOR DISTRICT - Rendi Wahyudi; Agus Budiman (Journal of Dance and Dance Education Studies, 2024)
The development of information technology in the 21st century, especially through the use of mobile phones in education, has had a significant impact. One of the prominent innovations is the use of social media as a tool for communication and self-expression for students. This study aims to determine how the use of TikTok social media can affect students' motivation and interest in learning dance in class X at SMA Bogor Regency. The research method uses a survey with a quantitative approach. The population consisted of 986 class X students from three high schools, namely SMAN 1 Tamansari, SMAN 1 Ciomas, and SMAN 1 Dramaga. The respondent sample was taken based on simple random sampling calculations to represent the population studied. Primary data collection techniques used interviews and questionnaires, while secondary data were obtained through documentation and literature studies. Data analysis includes normality tests, linearity tests, Pearson Product Moment correlation analysis, regression, and coefficient of determination. The results of the study showed a significant relationship between the use of TikTok social media and students' motivation and interest in learning (sig. 0.048 0.05 for learning motivation and sig. 0.044 0.05 for learning interest). Regression analysis shows that every 1% increase in the use of TikTok social media increases learning motivation by 1.011 and learning interest by 1.158. The coefficient of determination shows that TikTok social media has an influence of 3.9% on learning motivation and 4.1% on students' learning interest.